Approaches for integrating evidence of the effectiveness of actions in conservation funding to inspire more effective practice - Nida Al‐Fulaij; Pamela Abbott; Alex Bowmer; David Cope; Tiago deZoeten; Guy Foulks; Winifred F. Frick; Stephan M. Funk; Douglas Gibbs; Lauren Gupta; Nicolas Heard; Becky Holmes; et al. (Ecological Solutions and Evidence)
Abstract In the midst of a biodiversity crisis, it is critical that commonly used interventions to protect wildlife and recover losses are effective and learnings are widely shared. It is acknowledged that considerable gains could be made for society and biodiversity if conservation practices build on existing evidence of effectiveness. While funders can have a positive effect on conservation by funding effective conservation actions, their potential role in changing common practice is less well acknowledged. We believe that those providing funds could have a significant impact on the use of evidence, and thus practice, by encouraging and demonstrating best practice. We represent 18 funder organisations that ask applicants to reflect on and present available evidence, when requesting financial support, to justify why they believe their suggested management actions are likely to be effective. We use a variety of approaches to encourage and ensure the integration of evidence and provide the details of those here to encourage adoption (and adaption) by other funders. They range from simple requests for evidence in application forms to substantial support in designing a project (potentially including testing an action where evidence is lacking), depending on the scale, length and topic of proposed work. Reflecting on our experiences, we provide recommendations to help other funders adopt a more evidence‐based approach. These include considering how funders could improve funding impact, communicating with other funders to learn and adapt and the need to provide support to grantees to access evidence of effectiveness, explain different evidence types, how to use evidence in different contexts and what to do when no evidence exists. Practical implication. Funders have a unique role in setting expectations, providing guidance and helping advance how we do conservation work, through a unified approach. The gains we envisage from widespread adoption of funders asking for evidence of actions are that conservationists become used to reflecting on available evidence when planning projects and it becomes easier for funders to select and support effective approaches and evidence‐led practitioners. As conservation practice becomes increasingly professional and impactful, more funders will be attracted, ensuring even greater effectiveness.